Manajemen Pengembangan Karir Pranata Laboratorium Pendidikan di IAIN Kerinci - Rizki Gusmanto; Ahmad Yani (CV. ITTC INDONESIA, 2026)
Career development is a crucial aspect of human resource management in higher education institutions, and this is no exception for Educational Laboratory Technicians (PLP). This study aims to examine how the management of PLP career development is carried out at IAIN Kerinci, highlighting the practices of planning, implementation, and evaluation that shape the career paths of PLP. Using a qualitative approach, this study collected data through in-depth interviews with PLPs, their immediate supervisors, and human resources managers, supplemented by document analysis and observations in the laboratory setting. The results of the study indicate that career development for PLPs at IAIN Kerinci is underway but still faces a number of challenges, From a planning perspective, PLPs’ career choices are driven more by the alignment of their educational backgrounds with available recruitment opportunities than by structured long-term career planning. Meanwhile, work assignments through performance-based contracts have provided PLPs with opportunities to develop competencies in their respective fields, although these assignments remain focused on meeting operational needs. Other findings reveal that the level of self-directed career development among PLPs is quite high, as reflected in their active participation in training and certification programs, whether facilitated by the institution or pursued independently. However, the performance evaluation system and training programs organized by the institution remain general in nature and have not yet been fully integrated as strategic instruments for career development. In addition, career development policies for PLP. Specifically in terms of systematic career planning, inclusive policies for all employment statuses, and the optimization of evaluation and training systems that truly target competency needs. The results of this study are expected to serve as input for policymakers at IAIN Kerinci and other Islamic higher education institutions in designing career development strategies for PLP that are more focused, equitable, and sustainable.